Safety and efficacy of iron isomaltoside 1000/ferric derisomaltose versus iron sucrose in patients with chronic kidney disease: the FERWON-NEPHRO randomized, open-label, comparative trial. Issue 1 (12th February 2020) - Bhandari, Sunil; Kalra, Philip A; Berkowitz, Mario; Belo, Diogo; Thomsen, Lars L; Wolf, Myles
Abstract: Background: The optimal intravenous (IV) iron would allow safe correction of iron deficiency at a single infusion over a short time. The FERWON-NEPHRO trial evaluated the safety and efficacy of iron isomaltoside 1000/ferric derisomaltose (IIM) in patients with non-dialysis-dependent chronic kidney disease and iron deficiency anaemia. Methods: In this randomized, open-label and multi-centre trial conducted in the USA, patients were randomized 2:1 to a single dose of 1000 mg IIM or iron sucrose (IS) administered as 200 mg IV injections up to five times within a 2-week period. The co-primary endpoints were serious or severe hypersensitivity reactions and change in haemoglobin (Hb) from baseline to Week 8. Secondary endpoints included incidence of composite cardiovascular adverse events (AEs). Results: A total of 1538 patients were enrolled (mean estimated glomerular filtration rate 35.5 mL/min/1.73 m 2 ). The co-primary safety objective was met based on no significant difference in the incidence of serious or severe hypersensitivity reactions in the IIM and IS groups [0.3% versus 0%; risk difference: 0.29% (95% confidence interval: –0.19; 0.77; P > 0.05)]. Incidence of composite cardiovascular AEs was significantly lower in the IIM versus IS group (4.1% versus 6.9%; P = 0.025). Compared with IS, IIM led to a more pronounced increase in Hb during the first 4 weeks (P ≤ 0.021), and change in Hb to Week 8 showed non-inferiority, confirming that the co-primary efficacy objective was met. Conclusions: Compared with multiple doses of IS, a single dose of IIM induced a non-inferior 8-week haematological response, comparably low rates of hypersensitivity reactions, and a significantly lower incidence of composite cardiovascular AEs. Graphical Abstract: